Reading Agnes: The Rhetoric of Gender in Ambrose and Prudentius - Burrus, Virginia (Journal of early Christian studies, 1995)
Readings of two late fourth-century versions of the tale of the virgin martyr Agnes illumine the place of gender within a late ancient Christian discourse that locates itself in complex relation to both a Christian and a classical past. In Ambrose's account, the tale of Agnes, juxtaposed with that of Thecla, constitutes a reworking of the apocryphal tale of the conversion and witness of a sexually continent woman. In Prudentius' text, allusions to the virginal heroine of classical tragedy represent Agnes as a new Polyxena. Through such intertextual play, the ambiguously gendered virgin martyr emerges not only as a model for the disciplining of the would-be virago of female asceticism but also as a representation of the "body" of a discourse of orthodoxy that deploys the dual rhetorics of martyrdom and empire, inscribing itself as feminine in an ascetic subversion of the masculine discourse of clssical speech, whereby the transcendently male authority of this Christian discourse is paradoxically asserted.